Increased prevalence of fungemia in Medina, Saudi Arabia - Khateb, Aiah M.; Alofi, Fadwa S.; Almutairi, Abdullah Z. (Frontiers in Epidemiology, 2023)
Abstract Background: The prevalence of fungal infection is increasing globally due to the increase in immunocompromised and aging population. We investigated epidemiological changes in fungemia in one of the major centers in Medina over seven years period with 87447 admissions. Methods: Retrospective search of records for causative agents of fungemia in inpatients at King Fahad Hospital (KFH) between the years 2013-2019. Fungal positive blood cultures and demographic, and treatment data were extracted. Results: A total of 331 fungemia episodes were identified in 46 patients proven by blood culture. The annual prevalence of fungemia has increased from 0.072 in 2013 to 1.546 patients/1000 in 2019. The mean age of fungemia episodes was 56 years old and 62% of episodes were in females. Samples from central blood incubated aerobically were the highest accounting for 55% (n=182). Among yeast species Candida parapsilosis recorded the highest number of episodes 37% (n=122), followed by Candida glabrata 32% (n=107), Candid albicans 29% (n=94), Cryptococcus neoformans 1% (n=4). Among mould, Lichtheimia (Absidia) species was the most common 1% (n=3). Yeast-like fungi Trichosporion mucoides 0.003% (n=1). The use of Antifungal treatments has increased (96%) over the years 2013-2019. An increase in resistance rate of 2% was found in C. albicans and C.glabrata. The highest comorbidities were recorded included renal disease (24.2%). Conclusions: C. parapsilosis was the leading cause of fungemia. Renal diseases association with increased Candidemia was alarming. This study is a fundamental resource to establish management policies for fungal infection in the region.